THE INFLUENCE OF CAREER DEVELOPMENT, JOB TRAINING AND ORGANIZATIONAL CULTURE ON PERFORMANCE THROUGH JOB PROMOTION - Runi Ayu Kusumaningrum (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2026)
The purpose of this study is to determine and analyze the influence of career development on performance in members of the Directorate of Narcotics Investigation of the DIY Regional Police, to determine and analyze the influence of job training on performance in members of the Directorate of Narcotics Investigation of the DIY Regional Police, to determine and analyze the influence of organizational culture on performance in members of the Directorate of Narcotics Investigation of the DIY Regional Police, to determine and analyze the influence of career development on job promotion in members of the Directorate of Narcotics Investigation of the DIY Regional Police, to determine and analyze the influence of job training on job promotion in members of the Directorate of Narcotics Investigation of the DIY Regional Police, to determine and analyze the influence of organizational culture on job promotion in members of the Directorate of Narcotics Investigation of the DIY Regional Police, to determine and analyze the influence of performance on job promotion in members of the Directorate of Narcotics Investigation of the DIY Regional Police. quantitative research, the population in this study were all members of the Directorate of Narcotics Investigation of the DIY Regional Police totaling 120 personnel, the sampling technique in this study was a saturated sampling technique. Thus the number of samples used was 120 respondents.